(untitled) (Research, Society and Development, 2020)
This study aimed to analyze research using vestibular evoked myogenic potentials (VEMP) in the typical developing child population, through a literature review. The search was carried out in Portal of Journals Capes, in July 2019. The Boolean operators used were vestibular evoked myogenic potentials (OR) VEMP (AND) children (OR) child, in the English language, without delimiting the date of publication, with the filters “type of material” and “descriptors in the title”. Papers that investigated the results of cervical and / or ocular VEMP in the child population with typical development were included. In general, researchers describe the VEMP as a well-tolerated test for screening vestibular function in young children, fast and with reproducible results. Latencies may be lower in children compared to adults, although there is no significant difference in some results, which may be verified in future original studies with larger samples. The values can also vary according to the equipment, the transducer and the technique used.